Digital Promotion of Naruu Beach, Nias through English Content on Instagram and TikTok - Afore Tahir Harefa; Etis Bago; Heppy Vitasari Gulo; Des Asnidar Lase; Merlina Halawa (Arus Jurnal Psikologi dan Pendidikan, 2026)
This study examines the role of English-language digital content on Instagram and TikTok in promoting Naruu Beach, Nias, as an emerging tourism destination. The rapid growth of visual-based social media has transformed destination marketing strategies, enabling lesser-known destinations to reach global audiences more effectively. Employing a qualitative descriptive research design supported by descriptive quantitative analysis, this study analyzes English-language promotional content published on Instagram and TikTok, focusing on content characteristics, storytelling strategies, visual presentation, and audience engagement metrics. Data were collected through systematic observation and documentation of relevant social media posts, including videos, captions, hashtags, and engagement indicators such as views, likes, comments, and shares. The findings indicate that the use of English as a global communication medium enhances international accessibility and destination visibility. Instagram content primarily contributes to destination image formation through visual aesthetics, while TikTok demonstrates stronger potential in expanding reach due to its algorithm-driven distribution and trend-based short videos. However, the results also reveal limitations in branding consistency, interactive engagement, and narrative depth. Despite these challenges, English-language short-form video content on Instagram and TikTok presents a cost-effective and strategic approach for promoting Naruu Beach in the global tourism market. This study contributes to digital tourism literature by providing empirical insights into social media-based promotion for emerging destinations and offers practical implications for sustainable destination marketing strategies.